2002
DOI: 10.1001/archsurg.137.5.585
|View full text |Cite
|
Sign up to set email alerts
|

Blunt Lower-Extremity Trauma and Popliteal Artery Injuries

Abstract: Abandoning mandatory angiography in patients with blunt lower-extremity trauma and normal neurovascular examination results does not affect limb salvage.Design: Retrospective, nonrandomized cohort study. Mean follow-up (31 of 52 patients) of 9.5 months (range, 0-96 months).Setting: Single-institution, academic level I trauma center.Patients: Medical records of patients presenting emergently with knee dislocation, distal femoral fractures, or proximal tibial fractures during a 20-year period were reviewed. Fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 17 publications
1
45
0
5
Order By: Relevance
“…The complete absence of pulses is an uncommon and very late finding in compartment syndrome; whereas absent pulses seen immediately after blunt lower extremity trauma mandate immediate evaluation for vascular injury. Absent pulses are 58 -80% specific for vascular injury in blunt trauma (6,(13)(14)(15)(16)(17). Ultimately, it was thought that the compartment syndrome was a complication resulting from the popliteal artery injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete absence of pulses is an uncommon and very late finding in compartment syndrome; whereas absent pulses seen immediately after blunt lower extremity trauma mandate immediate evaluation for vascular injury. Absent pulses are 58 -80% specific for vascular injury in blunt trauma (6,(13)(14)(15)(16)(17). Ultimately, it was thought that the compartment syndrome was a complication resulting from the popliteal artery injury.…”
Section: Discussionmentioning
confidence: 99%
“…Absent pedal pulses or signs of distal ischemia mandate immediate angiography with vascular surgery consultation. Failure to revascularize within 6 -8 h results in an unacceptably high amputation rate (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Peroneal nerve injuries are less common than popliteal artery injuries because the nerves are not as tightly anchored; however, when nerve injury is present, a concomitant vascular injury must be suspected as it is more likely to be present.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a strong correlation between physical findings and abnormalities observed on catheter angiography. 1,7,14 Furthermore, another study has concluded that the selective use of lower limb angiography, based on physical findings, is sufficient in patients with severe blunt lower limb injury. 10 Non-invasive imaging modalities such as arterial duplex examination and CT angiography allow accurate assessment of arterial trauma without the need for invasive catheter angiography and its inherent complications.…”
Section: Discussionmentioning
confidence: 99%
“…• intracranial bleeding sources: aside from acute epidural hematoma from arterial bleeding sources (see above), dural sinus bleeding may represent a major source of intracranial hemorrhage requiring immediate surgical intervention by trepanation and craniotomy [65]. • penetrating and blunt vascular injuries, "mangled extremity": arterial injuries with clinical signs of limb ischemia due to blunt or penetrating trauma require immediate surgical management without further diagnostics [72][73][74]. The "Mangled Extremity Severity Score" (MESS) has been established as a guideline for early determination whether limb salvage is achievable as opposed to early amputation, with an established "cutoff" level of the MESS at 7 points [75][76][77][78][79].…”
Section: The Concept Of "Damage Control"mentioning
confidence: 99%